Imaging of groundwater contamination using 3D joint inversion of electrical resistivity tomography and radio magnetotelluric data: A case study from Northern India. Issue 3 (1st March 2020) - Devi, A.; Israil, M.; Singh, A.; Gupta, Pravin K.; Yogeshwar, P.; Tezkan, B.
ABSTRACT: The impact of untreated sewage irrigation and waste disposal practices on groundwater is investigated by 3D joint inversion of radio magnetotelluric and electrical resistivity tomography data. In this case study, electrical resistivity tomography and radio magnetotelluric field measurements were carried out on several profiles near a waste disposal site which was irrigated with untreated sewage water for agriculture purpose. In addition, radio magnetotelluric and electrical resistivity tomography measurements were carried out, far away from the waste site, to derive the uncontaminated geology. The data were analysed earlier using 2D inversion techniques. However, for the 2D inversion of the electrical resistivity tomography and radio magnetotelluric data, assumptions about the strike direction are required. As no clear strike direction is evident for the contamination, we considered the problem as 3D and interpreted the present data set using the 3D inversion algorithm 'AP3DMT‐DC'. The inverted 3D resistivity model shows an unconfined aquifer of low resistivity which is overlain by an unsaturated slightly resistive near surface formation. With increasing distance from the waste sites, an increase in the resistivity of the shallow unconfined aquifer is observed. Furthest away from the waste site undisturbed geology is expected. We derived consistent and meaningful 3D resistivity models. The uncontaminated reference site indicates an increased resistivity for the aquifer layer. A synthetic 3D study was carried out to demonstrate and validate algorithm performance as well as convergence capabilities. The study demonstrates that the two methods, electrical resistivity tomography and radio magnetotelluric, complement each other. Besides, a better resolved inverted model is obtained through a 3D joint inversion, in comparison to individual 2D and 3D inversions.